(3GdJYde YfO GdZRGdj (B/s - (3GdHNGQj,MeGfI s ((3GdLRGFQ (B:s (3GdeDSSI GdhWfjI ddcJGH(B;(3eWHYI GdfNdI ,s, 1991)
(3JCJj OQGSI GdJYde YfO GdZRGdj (B,(3CHQR GdTNUjGJ GdSfjI aj GdESdGe ceMGhdI ddcTa Yf ehba CMO CFeI GdeSdejf h eacQjge ef gPG GdehVhY hdHjGf eOi ChLg GdLOI h GdCUGdI GdJj CJi HgG(B, (3hSHbg ddYOjO ef GdYdeGA GdeYGUQjf hGdeMOKjf aj CcKQ ef ejOGf ajg ceG JCJj gPg GdOQGSI dcTa heMGhdI JHOjO YbOJjf NWQJjf Yf CUMGHgeG YbOI Jahb hYbOI fbU DJdc GdYbOJGf GddJGf XdJG JMceGf ehGba HYV (B-(3GdeKbajf(B-(3GdPj jMSHhf Ydi GdYGde GdYQHj h GdESdGej h JJMceGf aj fXQI HYV GdeacQjf h GdHGMKjf ef ZjQ GdeSdejf ddMVGQI GdGSdGejI GdYQHjI (B.s
Keywords: (3GdZRGdj s; (3GdJYdes